Clinical and Radiological Features of Adult Onset Bilateral Medial Frontal Cerebral Cortical Encephalitis With Anti-myelin Oligodendrocyte Glycoprotein Antibody - Fujimori, Juichi; Nakamura, Masashi; Yagihashi, Takahito; Nakashima, Ichiro (Frontiers in Neurology, 2020)
Objective: To clarify the clinical and radiological features of adult onset anti-myelin oligodendrocyte glycoprotein (MOG) antibody-associated bilateral medial frontal cerebral cortical encephalitis (BFCCE) and discuss its pathogenesis. Methods: We systematically reviewed the literature for patients with anti-MOG antibody-associated BFCCE. Patients who were also positive for other encephalitis-related autoantibodies were excluded from the study. The frequency of several characteristic neurological symptoms and lesion distributions were analyzed, and the pathogenesis based on MRI imaging findings was discussed. Results: We identified 6 patients with anti-MOG antibody-associated BFCCE. Among them, 6/6 had headache, 4/6 had fever, 3/6 had seizure, 2/6 had paraparesis, 2/6 had lethargy, and 2/6 had memory disturbance. CSF pleocytosis was observed in 5/6 patients, while CSF myelin basic protein was not elevated in any of the 6 patients. On brain MRI, 6/6 had bilateral medial frontal cortical lesions, 3/6 had corpus callosum lesions, and 3/6 had leptomeningeal enhancements. Most of the lesions were distributed in the territory of the anterior cerebral artery (ACA). Conclusion: Our results indicate that anti-MOG antibody-associated BFCCE presents with characteristic clinical symptoms and MRI findings, which might reflect lesion formation in the ACA territory.